Disposal of solid waste from the perspective of Science, Technology, Society and Environment for Science Teaching: A systematic literature review (Research, Society and Development, 2021)
In view of the constant environmental concerns in teaching for sustainability, with the intention of protecting rivers and oceans and improving the quality of life, the need to contextualize teaching for scientific literacy is evident. This article is a brief systematic review of the literature within the Portal CAPES periodicals, considering that it is known as one of the main virtual resources of academic research. A survey was carried out on the theme of household solid waste disposal as a generating theme within the perspective of the Science, Technology, Society and Environment (CTS/CTSA) approach. The objective was to address the relationship between the disposal of waste as a socio-environmental theme with the scientific literacy of students through the CTS/CTSA approach. The methodology consists of a systematic literature review, a theoretical study where 3 articles published over the period from 2016 to 2020 were found, with educational approaches that cover the theme of contextualization of waste disposal, in order to identify the research contributions related to this subject. Finally, a data analysis was carried out through a qualitative documental analysis. Therefore, the need for further studies within this theme was highlighted, with the purpose of keeping the CTS/CTSA movement alive as well as contributing to a society with quality and sustainable education.